E-Masjid marketplace: my masjid portal - Osman, Mohd Aidil; Zainudin, Muhammad Afdhaluddin; Mohd Ashri, Mohamad Azammunir; Wan Razali, Wan Shakrawi; Mohamad Fauzi, Muhammad Amirul Ashraf; Ahmad Dahlan, Abdul Rahman (Eclat Research Publication, 2016)
This project called MyMasjid Portal shall initially promote Masjid not only a place for ibadah but also a place that can obtain revenue for the Masjid organization and society. The project use portal site and surrounded Masjid area as the main medium platform in order to integrate business and ibadah among Muslim. There are many activities planned in this project such as are online auction and ads, sales and carnival and many more. This project in the future will be considered to involve many Masjids in the peninsular of Malaysia. It will encourage the government, Islamic NGOs and all the Masjid organization to get involve in order to help the Masjid to produce their own revenues. Hence, it will increase the business activities and produce income to our country. When this project becomes organized properly and well-equipped, a step further is to extend this project to the national level that has been the main objective for this project. As the result, the Masjid organization independently can run these revenues activities on their own. In conclusion, this paper proposed MyMasjid Portal to raise the income growth of all Masjids in peninsular of Malaysia, as well as to the society involved.